Threats to The Meritocracy and Neutrality of State Civil Apparatus - Ramadhan, Muhammad Nur (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
The dissolution of the Indonesian Civil Servant Commission (KASN) is a setback for bureaucratic reform. It has raised a serious concern about the future of the meritocracy and neutrality of state civil apparatus (ASN) in Indonesia. An independent supervisory institution, KASN followed the principles of meritocracy by ensuring that the recruitment, promotion, and transfer processes of ASN were based on competence and performance. Dissolving KASN through poor legislation is questionable. This normative legal article employed the qualitative approach, using primary legal sources, such as laws and regulations and other types of policy. In addition, it used secondary legal sources, e.g., literature and other valid and relevant information. Therefore, this research is prescriptive and analytical. This article discusses the impacts of the dissolution of KASN on Indonesia's bureaucracy and the urgency of continuing meritocratic supervision to ensure that ASN remains professional and free from political pressure.